(untitled) (Al-Academy, 2017)
The body of the actor and its expressive significance is an essential topic in studying acting . it is not only confined to the study of soul and body from philosophical aesthetic perspective , but also to study the conception and mechanism of such a dichotomy followed by theatre directors and theorists , who are highly concerned with the creativity of actors . The researchers believe that such a study would be of benefit for actors as well as others working in theatre . The study falls into two sections . the first deals with the philosophical aspects of the soul and body dichotomy . It is concerned with reviewing the opinions of a number of Greek and Moslem philosophers as well as contemporary ones as regards the concept and working of soul and body dichotomy . The second section examines the soul and body dichotomy in the thoughts of directors and theorists . It is an attempt to find relations between the ideas of workers ion theatre and those of philosophers to arrive at indicators in the light of which the analytic tools are developed to examine the sample .